Learning healing relationality: Dynamics of religion and emotion - Utriainen Terhi (Routledge, 2025)
This chapter approaches religion – and specifically present-day lived religious expression – from the perspective of emotions and learning to work with emotions. The particular emphasis is an approach that understands emotions as dynamic ways to relate to the self, different kinds of others, and the world. This relationality is in many more or less subtle ways enhanced, guided and regulated by religious teachings and rituals. The dynamics of religion and emotion are also strongly present in contemporary forms of “spirituality” that are closely connected to a wider therapeutic culture offering countless methods and pedagogies for individuals to learn to tend to their emotions, and to enhance their emotional lives (see, Wilce and Fenigsen 2016). After discussing the complex conjunction of religion and emotion and several theoretical ways of framing and approaching this conjunction, I provide an ethnographic case-study involving Finnish women engaging angel-spirituality as an example of a globalizing religious culture in which emotions receive attention as key to self-understanding and as dynamic relations between human and super-human others and, ultimately, with the whole universe. As June McDaniel (2004: 266) writes, emotion in religious life is not a passive response to the world, but an active engagement in it.
The Routledge Handbook of Language and Emotion